2011
DOI: 10.1371/journal.ppat.1002162
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Chemokine Sequestration by CrmD, a Poxvirus-Encoded Tumor Necrosis Factor Receptor

Abstract: Pathogens have evolved sophisticated mechanisms to evade detection and destruction by the host immune system. Large DNA viruses encode homologues of chemokines and their receptors, as well as chemokine-binding proteins (CKBPs) to modulate the chemokine network in host response. The SECRET domain (smallpox virus-encoded chemokine receptor) represents a new family of viral CKBPs that binds a subset of chemokines from different classes to inhibit their activities, either independently or fused with viral tumor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 59 publications
2
48
0
Order By: Relevance
“…Simply to block M-CSF:FMS signaling, a more direct approach and consequently a more efficient strategy would be for an EBV-encoded antagonist fully disguised as a receptor or ligand mimic to occupy the active surfaces required for signaling. This strategy has been used by various types of viruses in immune modulation, especially for sequestrating cytokines (27,28). In fact, when BARF1 first was identified as a binding partner for M-CSF, it was speculated to be an FMS homolog (13).…”
Section: Indirect Interference Of Barf1 With Mcsf:fms Binding and Sigmentioning
confidence: 99%
“…Simply to block M-CSF:FMS signaling, a more direct approach and consequently a more efficient strategy would be for an EBV-encoded antagonist fully disguised as a receptor or ligand mimic to occupy the active surfaces required for signaling. This strategy has been used by various types of viruses in immune modulation, especially for sequestrating cytokines (27,28). In fact, when BARF1 first was identified as a binding partner for M-CSF, it was speculated to be an FMS homolog (13).…”
Section: Indirect Interference Of Barf1 With Mcsf:fms Binding and Sigmentioning
confidence: 99%
“…An additional group, more recently described, includes the SECRET (Smallpox virus Encoded Chemokine Receptor) domain from the variola virus protein, CrmB and the ectromelia virus (EV) protein, CrmD (Antonets et al, 2010;Xue et al, 2011). These proteins each contain two domains, one that binds tumor necrosis factor and another named SECRET that binds, with variable affinity, to selected CC and CXC chemokines (Antonets et al, 2010;Xue et al, 2011). Viral CBKPs are thought to facilitate successful viral replication by reducing leukocyte activation and chemotaxis to the site of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Sequence conservation across the various vCKBPs is quite low (<15%) but structures, which have appeared for several members, often contain a characteristic b-sandwich topology, which has no resemblance to host proteins that bind chemokines (Alexander et al, 2002;Carfí et al, 1999;Bahar et al, 2008;Xue et al, 2011). The type-II CKBP family proteins, A41 and vCCI, have structures that are monomeric with a b-sandwich fold (Arnold and Fremont, 2006;Bahar et al, 2008;Carfí et al, 1999;Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De novo modeling of VARV CrmB SECRET domain spatial structure revealed structural homology with CPXV 35-kDa and VACV A41 proteins (Antonets et al, 2010). The three dimensional structure of the SECRET domain alone or complexed with a low affinity binding chemokine, CX3CL1, was solved and confirmed that it shares the same ␤-sandwich topology with the 35-kDa and A41 poxvirus CKBPs (Xue et al, 2011) (Fig. 2C).…”
Section: A Family Of Poxvirus Proteins Containing the Smallpox Virus-mentioning
confidence: 77%